Evaluation of the Antimicrobial Capacity of Bacteria Isolated from Stingless Bee (Scaptotrigona aff. postica) Honey Cultivated in Açai (Euterpe oleracea) Monoculture - Iago Castro da Silva; Eveson Oscar Almeida Conceição; Daniel Santiago Pereira; Hervé Rogez; Nilton Akio Muto (MDPI AG, 2023)
Many antimicrobial compounds have been seeking to protect the human body against pathogenic microbial infections. In recent times, there has been considerable growth of pathogens resistant to existing drugs due to the inappropriate use of antibiotics. In the present study, bacteria isolated from the honey of stingless bees native to the Amazon called Scaptotrigona aff. postica and Apis mellifera were used to determine their potential antimicrobial properties and characterize the medium cultivated with isolated bacteria. The results showed inhibition of nine isolates. Among these isolates, SCA12, SCA13, and SCA15 showed inhibitory activity similar to that of vancomycin, which was used as a positive control. The SCA13 strain obtained the best results with antimicrobial extract against the tested pathogens; the species was identified as Enterococcus faecalis, and its lyophilized extract was characterized by temperature, pH, and trypsin, in which they showed antimicrobial activity. This work shows that bacteria isolated from the stingless bee honey, Scaptotrigona aff. postica, have the potential to produce antimicrobial substances.